2017
DOI: 10.1002/adsc.201600980
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Route to Cyclopentenes from 1,6‐Enynes and Diazo Ketones through Gold and Rhodium Catalysis

Abstract: This work reports the construction of cyclopentene cores from 1,6‐enynes and aryl diazo ketones through two new reaction sequences involving initial gold‐catalyzed cyclization of 1,6‐enynes with diazo species, followed by rhodium‐catalyzed skeletal rearrangement of the resulting 3‐cyclopropyl‐2‐en‐1‐ones. In most instances the rhodium‐catalyzed reactions afforded cyclopentene derivatives whereas several n‐alkyl‐ or ortho‐substituted phenyl ketones delivered seven‐membered oxacycles. A plausible mechanism provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 87 publications
1
9
0
Order By: Relevance
“…Later, Liu and co-workers reported that cyclopropyl gold carbenes generated in a 5- exo -dig fashion from 1,6-enynes can be trapped by aryl diazo ketones ( Scheme 35 B). 391 …”
Section: Construction Of 3-membered Rings Catalyzed By Goldmentioning
confidence: 99%
“…Later, Liu and co-workers reported that cyclopropyl gold carbenes generated in a 5- exo -dig fashion from 1,6-enynes can be trapped by aryl diazo ketones ( Scheme 35 B). 391 …”
Section: Construction Of 3-membered Rings Catalyzed By Goldmentioning
confidence: 99%
“…This Obound enolate has a 16-electron configuration, being favorable for the final reductive elimination that leads to oxepines 125. [53] Scheme 29. A sequential route to oxepines 125 from 1,6-enynes 122 and diazo ketones 123 through gold and rhodium catalysis.…”
Section: Eurjocmentioning
confidence: 99%
“…Adapted from ref. [53] In 2018, Hawkins and co-workers, exploited a method previously developed by them, [54] in combination with a cyclization under Mitsunobu conditions, [55] to get access to the oxepinefused flavone 133. [56] As depicted in Scheme 30, the first reaction transforms the cyclopropane 132 into the alcohol 137.…”
Section: Eurjocmentioning
confidence: 99%
See 1 more Smart Citation
“…А number of different combination of solvents, bases and reaction conditions were described in literature for this condensation. For example, t -BuOK in benzene [16], NaOMe in methanol [17], NaH in Et 2 O [18], NaH in THF [19], NaOMe in Et 2 O [20] or LiHMDS in THF [21] were tested. The yields varied from 32 to 87%.…”
Section: Introductionmentioning
confidence: 99%